Unraveling The Nephroprotective Potential of Curcuma zedoaria Against Chronic Kidney Disease: A Network Pharmacology Approach - Harahap , Emirsyah; Nadapdap, Thomson Parluhutan; Nasution , Ali Napiah (Fakultas Farmasi, Universitas Surabaya, 2025)
Chronic kidney disease (CKD) remains a major global health concern with limited treatment options. Curcuma zedoaria , a traditional medicinal plant, has shown potential in managing inflammatory and oxidative stress-related conditions. This study aimed to explore its nephroprotective mechanisms through a network pharmacology approach. A total of 12 bioactive compounds were identified from C. zedoaria and screened for drug-likeness. SwissTargetPrediction revealed multiple molecular targets, with curdione, dehydrocurdione, and curcumin showing the highest connectivity. Integration with CKD-associated genes from GeneCards and GSE66494 datasets yielded 241 common targets. Using Cytoscape, a compound–target–disease network was constructed, highlighting key biological processes such as inflammation, apoptosis, and fibrosis. PPI analysis identified top hub proteins including HSP90AA1, STAT3, SRC, AKT1, MAPK1, and MAPK3. Functional enrichment via GO and KEGG pathways revealed significant involvement of EGFR tyrosine kinase inhibitor resistance and HIF-1 signaling pathways. These findings suggest that C. zedoaria exerts protective effects through a multitarget mechanism modulating critical pathways in CKD progression. This study provides a theoretical basis for further experimental validation and supports the potential use of C. zedoaria as a complementary therapy in CKD management. Submitted: 21-05-2025, Revised: 15-06-2025, Accepted: 17-06-2025, Published regularly: June 2025